The psychological loneliness and its relation with the future anxiety and psychological alienation of the university student - عزوز, اسمهان (مجلة دراسات في سيكولوجية الانحراف, 2022)
This study aims at shedding light on the relation between the psychological loneliness, the psychological alienation, and future anxiety of a sample of students at the University of Mohamed Lamine Debbaghine of Setif 02. Thus, we used the correlation descriptive method on a sample of 124 students (males and females) at the Department of Psychology. Our findings show a low level of the feeling of psychological loneliness of the students and a high feeling of future anxiety and psychological alienation. In addition, there is no correlation between the feeling of the psychological loneliness, the psychological alienation, and the future anxiety. Based on these results, we recommend building therapeutic plans and programs to reduce the level of the future anxiety and the psychological alienations of the students